Foot use during vertical climbing in chimpanzees (Pan troglodytes). Issue 109 (August 2017) - Wunderlich, R.E.; Ischinger, S.B.
Abstract: Upright bipedalism is a hallmark of hominin locomotion, however debates continue regarding the extent of arboreal locomotion and the nature of bipedalism practiced by early hominins. Pedal form and function play a prominent role in these debates, as the foot is the element that directly interacts with the locomotor substrate. Recent finds have substantially increased the availability of associated foot remains of early hominins and emphasized the enigmatic nature of the early evolution of human bipedalism. New discoveries of associated forefoot remains have afforded the opportunity to assess relative proportions across the forefoot of fossil hominins and illuminated the need for data on relative loading across the forefoot in extant hominoids. In order to provide functional data with which to examine the relationship between bony features and load distribution across the forefoot during climbing, we present the first analysis of plantar pressure distribution across the forefoot of chimpanzees climbing a vertical support. Chimpanzees load the medial metatarsals and first toe disproportionately during vertical climbing. Peak pressures on these elements occur at the end of stance phase during climbing and are higher than on any other elements of the foot. Toe pressures are considerably higher during vertical climbing than during knuckle-walking or movement on horizontal poles, supporting the notion that the plantarly-broad and dorsally-narrow metatarsal heads in chimpanzees and some early hominins are associated with close-packing of the metatarsophalangeal joint during climbing.